2020
DOI: 10.20473/jvhs.v3.i3.2020.89-96
|View full text |Cite
|
Sign up to set email alerts
|

Noise and Subjective Complaints of Workers as Effort to Control the Occurrence of Noise Induced Permanent Threshold Shif (Nipts)

Abstract: Background: Timber industry is one industry that has experienced an increase in noise levels as a result of the presence of modern machines, higher speeds, and more levels so that the risk of workers experiencing hearing loss due to noise can increase as the occurrence of Noise-Induced Permanent Threshold Shif (NIPTS). Purpose: The purpose of this study is to analyze the risk factors associated with subjective complaints of workers due to noise at work and formulate control measures to prevent the occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
1
0
1
Order By: Relevance
“…The frequency and depth of diving performed by traditional diving fishermen will also affect the occurrence of ear barotrauma which can cause hearing loss 18,19,20 . This is in accordance with research on the description of hearing loss in diving activities, namely the longer and the deeper the dive, the greater the risk of hearing loss 41 .…”
Section: Discussionsupporting
confidence: 91%
“…The frequency and depth of diving performed by traditional diving fishermen will also affect the occurrence of ear barotrauma which can cause hearing loss 18,19,20 . This is in accordance with research on the description of hearing loss in diving activities, namely the longer and the deeper the dive, the greater the risk of hearing loss 41 .…”
Section: Discussionsupporting
confidence: 91%
“…Another previous study showed there was a significant relationship between the intensity noise with complaints of hearing loss in workers (Wardani, et al , 2020). Risk factors that affect the severity of deafness include noise intensity, frequency, duration of exposure per day, work period, sensitivity of individuals, age and other factors that can cause deafness.…”
Section: Complaints Of Hearing Disordersmentioning
confidence: 96%
“…Communicate " Hari Pendengaran Sedunia 2021 merupakan usaha untuk mengingatkan kepada masyarakat tentang Pendengaran menyajikan seruan aksi global untuk mengatasi gangguan pendengaran dan penyakit telinga di sepanjang kehidupan. Beberapa kata kunci dari target Hari Dengar Pendapat Dunia 2021: (1) Pembuat kebijakan, (2) semakin banyakaknya Jumlah orang yang hidup dengan gangguan pendengaran dan penyakit telinga yang belum terselesaikan (Wardani et al, 2020), (3) Tindakan tepat waktu diperlukan untuk mencegah dan mengatasi gangguan pendengaran di sepanjang kehidupan, (4) Berinvestasi dalam intervensi yang hemat biaya akan menguntungkan orang-orang dengan gangguan pendengaran dan membawa keuntungan finansial bagi masyarakat(Armia Putri et al, 2021), ( 5) Mengintegrasikan perawatan telinga dan pendengaran yang berpusat pada orang dalam rencana kesehatan nasional untuk cakupan kesehatan universal, ( 6) Kesadaran masyarakat umum terkait fungsi pendengaran (Susiyanti et al, 2020).…”
Section: [Jurnal Kreativitas Pengabdian Kepada Masyarakat (Pkm) P-iss...unclassified